Bioassays with freshwater snails Biomphalaria sp.: from control of hosts in public health to alternative tools in ecotoxicology. Issue 1 (2nd January 2017) - Oliveira-Filho, Eduardo Cyrino; Nakano, Eliana; Tallarico, Lenita de Freitas
Abstract: Ecotoxicology is the science responsible for the study of the adverse effects of chemicals on ecosystems considering biotic and abiotic components. Several invertebrate groups have long been used to evaluate the aquatic toxicity of chemical compounds. Among these organisms, the microcrustaceans are the most recommended in Brazilian and international protocols (e.g. Daphnia sp. and Ceriodaphnia sp.). Until the beginning of the 1990s, the use of mollusks with ecotoxicological purposes was non-existent, except for the species tested as target of molluscicides in public health studies. Since the second half of this same decade the tests with mollusks have begun to be disseminated in several countries, valuing endemic species and especially the scarcity of test species in benthic habitats. In the early 2000s, with the disclosure of the harmful effects of pollutants with endocrine disrupting properties, gastropods have begun to be used not to evaluate lethal effects, but rather to observe physiological effects such as reproduction and embryonic development. Since then, assays with these approaches, especially with freshwater snails Lymnaea stagnalis and Biomphalaria sp., have been considered to be innovative and highly sensitive, often more than those achieved with traditional groups of test organisms in ecotoxicology (such as microcrustaceans and fishes).